(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Arthritis is a form of joint disorder that involves inflammation of one or more joints. It is very common condition especially in women and older people. Ayurveda has contributed a lot for the management of arthritic conditions. The plant Bala, identified as Sida cordifolia Linn. is a widely used drug in many of the Ayurvedic formulations especially in those for arthritic conditions. Kashaya (decoction) is one of the commonly prescribed preparations in Ayurveda. Present study was aimed to assess the anti-arthritic activity of Kashaya (decoction) of root of Sida cordifolia Linn. by inhibition of protein denaturation method and Inhibition of proteinase enzyme activity. Kashaya of roots of Bala was prepared as per standard procedure and was used to induce protein denaturation in Bovine serum albumin and to inhibit the activity of proteinase enzyme, trypsin. The absorbance was read by spectrophotometer to evaluate the percentage of inhibition in both the procedures. Each experiment was done in triplicates. The results were compared with standard drug Diclofenac sodium. Sida cordifolia Linn. showed dose dependent inhibitory activity and highest activity was seen in 500µg/ml concentration in both the experiments. The result showed that root of Sida cordifolia Linn. is having anti-arthritic property. Further studies can be carried out with other formulations of Bala like Choorna (powder), Swarasa (juice) etc. to compare their anti-arthritic activity. The study supports the classical use of plant Bala in various formulations in the treatment of arthritis.